(untitled) (Applied Biological Research, 2016)
The present study was conducted on the tongue of 18 goat foeti, divided into 3 prenatal age groups viz., group 1 (<50 days of gestation), group 2 (50-100 days of gestation) and group 3 (>100 days of gestation) containing 6 foeti in each group, to assess sequential events in the development of taste buds. The first appearance of primitive taste buds was observed on the apical surface of circumvallate and fungiform papillae in 93 days old goat foetus (CRL = 20.6 cm). The fungiform papillae located on the apex and body region of tongue were devoid of any taste buds. At 120 days of gestation (CRL = 31.1 cm), the taste buds were ovoid in shape and contained elongated or spindle shaped cells. The taste pores were apparent in taste buds at 146 days of gestation (CRL=35.5 cm).Themeannumberoftaste buds in circumvallate papillae in this group was 2.0±0.36. The mean number of taste buds in fungiform and circumvallate papillae in tongue of goat foeti in groupIII was 1.83±0.3 and 5.5±1.08, respectively. A significant increase in the number of taste buds was observed in circumvallate papillae between group II and III.